Evapotranspiration and crop coefficient of Basil determined by weighing lysimeters - Martins, Izabela P. [UNESP]; De Faria, Rogério T. [UNESP]; Palaretti, Luiz F. [UNESP]; Dos Santos, Miquéias G. [UNESP]; Filho, João Alberto Fischer [UNESP] (FapUNIFESP (SciELO), 2019)
The basil (Ocimum basilicum) crop is of great importance for trading as fresh or dried condiment for human consumption and essential oil for pharmaceutical and cosmetic industries. Water excesses and deficits can affect biomass production of plants, making it necessary to use the correct amount of water for each crop. Considering that determinations of water consumption and cultivation coefficients for medicinal plants are scarce, the aim of this study was determining evapotranspiration and crop coefficients of basil using lysimeters. The crop evapotranspiration was determined by weighing lysimeters for the replacements of 100, 75 and 50% of the maximum daily evapotranspiration. The reference crop evapotranspiration was estimated by the Penman-Monteith equation. Crop evapotranspiration for the 49 day cycle was 471, 352 and 236 mm, and daily rates ranged from 4.8 to 9.4; 4 to 8.1 and 3.7 to 7.4 mm/day, for the replacements of 100, 75 and 50% of the maximum daily evapotranspiration. Crop coefficients varied from 1.5 to 2.8 and were related to the days after transplanting, leaf area index, cover ratio and cumulative degrees-day.
Evapotranspiração e coeficiente de cultivo de manjericão determinados por lisímetros de pesagem
Keywords: Cover ratio; Crop coefficient; Medicinal plants; Ocimum basilicum; Water consumption